Ответы и объяснения

2013-11-10T06:55:00+00:00
62(1)
a-b * 3a^2   = -3a^2
        b(b-a)       b

62(3)
a^2-b^2      30a^2  =  (a-b)(a+b)         6a      =  a+b       6a    =  6a(a+b)
 25ab     *  (a-b)^2           5b      *   (a-b)^2        5b   *   a-b       5b(a-b)   

102(3)

4(c-2)+9(c+2)-12c-12  =  4c-8+9c+18-12c-12  =      c-2      =      1    
         12(c^2-4)                       12(c^2-4)            12(c^2-4)     12c+24
замучался перепечатывать)
Спасибо огромное, ты мне очень помог:))